Lace monitors scavenge the large carcass of an endangered eastern freshwater cod - Brendan C. Ebner; John St Vincent Welch; Leo M. Cameron; Jason Schaffer; Gavin L. Butler (Food Webs, 2026)

Otolith and Genomic Data Reveal Temporal Insights Into Stocking Across a Large River Basin in a Mobile, Long‐Lived Australian Freshwater Fish Species - Katherine A. Harrisson; Luciano B. Beheregaray; Christopher M. Bice; Emily J. Booth; Chris J. Brauer; Gavin L. Butler; David Dawson; Olga Dudchenko; Benjamin G. Fanson; Graeme Hackett; Annique Harris; Matthew J. Jones; et al. (Molecular Ecology, 2025)
Freshwater ecosystems and their biota are under increasing pressure from anthropogenic stressors. In response to declining fish stocks, hatchery and stocking programmes are widely implemented as core components of restoration and management strategies, with positive outcomes for some wild populations. Despite this, stocking remains contentious due to potential genetic and ecological risks to wild populations. Monitoring and evaluation of stocking outcomes are critical to ensuring the long‐term sustainability of wild populations, but identification of stocked individuals post‐release remains a key challenge, particularly for mobile species. In this study, we combined otolith (natal origin and age) and genomic data to identify stocked individuals and evaluate the genetic implications of stocking for a culturally and socioeconomically important and mobile freshwater fish, golden perch Macquaria ambigua (family: Percichthyidae), across Australia's Murray–Darling Basin (MDB). We also generated a chromosome‐level genome assembly. Many close kin were detected across the MDB, increasing in prevalence over recent decades and mostly of hatchery origin. Rivers with many close kin were associated with low effective population sizes ( N e

Corrigendum: Restoration of herbivory on Caribbean coral reefs: are fishes, urchins, or crabs the solution? - Mark J. Butler; Alain Duran; Colette J. Feehan; Alastair R. Harborne; Alwin Hylkema; Joshua T. Patterson; William C. Sharp; Angelo Jason Spadaro; Tom Wijers; Stacey M. Williams (Frontiers in Marine Science, 2025)

Corrigendum to “Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes” [Biol. Conserv. 300 (2024), 110843] - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2025)

Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2024)

Spatial variability in water strontium isotopes and trace metals from the Clarence River Basin, New South Wales, Australia - Lauren J. Stoot; Lee J. Baumgartner; Gavin L. Butler; Jason D. Thiem; Brett M. Knowles; Gregory S. Doran (Hydrobiologia, 2024)
Understanding fish movement in river systems is essential in identifying habitats which are important for species to perpetuate. Water chemistry, paired with fish otoliths, can be used to trace movements among different habitats, although a detailed understanding of spatial variation in water chemistry is first required. To obtain this knowledge, we analysed surface water collected from 59 sites throughout the Clarence River Basin, a coastal river basin in northern New South Wales, Australia. The primary objective was to quantify the spatial variation of trace metals and strontium isotope ratios ( 87 Sr: 86 Sr) for future and paired use with otolith microchemistry to track fish movement. Using ICP-OES, we identified that some trace metals, particularly strontium and barium as well as 87 Sr: 86 Sr ratios, varied spatially when analysing all water samples and revealed three distinct regions centring around the estuary, interior and outer regions. These differences were driven by variation in the underlying surface geology between the Clarence–Moreton Basin and the New England Block. Tidal influence also affected trace metals and 87 Sr: 86 Sr ratios throughout the estuarine area. We suggest that the level of differentiation identified in the current study has the potential to discriminate broad-scale fish movements among regions/habitats using otolith analysis, with fine scale movements best elucidated using complementary techniques.

Contribution of invasive carp (Cyprinus carpio) to fish biomass in rivers of the Murray–Darling Basin, Australia - Hayden T. Schilling; Gavin L. Butler; Katherine J. M. Cheshire; Dean M. Gilligan; Jerom R. Stocks; Jason D. Thiem; David A. Crook (Biological Invasions, 2024)
Following the introduction of the ‘Boolarra’ strain to Australia in the mid 1960’s, Common carp ( Cyprinus carpio ) rapidly spread in waterways across the Murray–Darling Basin (MDB) in southern-eastern Australia. A previous study of the population expansion based upon data up to the early 2000s suggested the carp population may have reached, and was fluctuating around, the ecosystem carrying capacity. It has been widely stated in the scientific literature and media that carp comprise up to 90% of fish biomass in MDB rivers; however, this figure is largely based on sparse data collected in the 1990s and the accuracy of this estimate is uncertain. Here, we analyse three decades (1994–2023) of electrofishing data to estimate the median proportion of total fish biomass contributed by carp across > 1,400 sites in lowland rivers ( 90%) by carp has declined from ≈ 33% of sites in the mid-1990s to ≈ 20% of sites. The proportion of biomass comprised by carp varied depending on the scale of analysis. Across the NSW MDB, carp accounted for a median of 57% (95% CI: 42.5–70.4) of fish biomass at the site level. At the river catchment scale estimates ranged from ≈ 45–66%. In contrast, the median proportion of carp within key rivers ranged from ≈ 46–80%, suggesting that carp can dominate total fish biomass in some rivers for short time-periods. The proportion of biomass contributed by carp at the NSW MDB scale was remarkably stable across decades, suggesting that the carrying capacity of carp may have been reached. Our revised estimates of the contribution of carp to overall fish biomass can facilitate informed debate around the dominance of carp in MDB rivers and provide important information for carp management in the future.

Complementary and Inducible creERT2 Mouse Models for Functional Evaluation of Endothelial Cell Subtypes in the Bone Marrow - Michael G. Poulos; Pradeep Ramalingam; Agatha Winiarski; Michael C. Gutkin; Lizabeth Katsnelson; Cody Carter; Laurence Pibouin-Fragner; Anne Eichmann; Jean-Leon Thomas; Lucile Miquerol; Jason M. Butler (Stem Cell Reviews and Reports, 2024)
In the adult bone marrow (BM), endothelial cells (ECs) are an integral component of the hematopoietic stem cell (HSC)-supportive niche, which modulates HSC activity by producing secreted and membrane-bound paracrine signals. Within the BM, distinct vascular arteriole, transitional, and sinusoidal EC subtypes display unique paracrine expression profiles and create anatomically-discrete microenvironments. However, the relative contributions of vascular endothelial subtypes in supporting hematopoiesis is unclear. Moreover, constitutive expression and off-target activity of currently available endothelial-specific and endothelial-subtype-specific murine cre lines potentially confound data analysis and interpretation. To address this, we describe two tamoxifen-inducible cre -expressing lines, Vegfr3-creER T2 and Cx40-creER T2 , that efficiently label sinusoidal/transitional and arteriole endothelium respectively in adult marrow, without off-target activity in hematopoietic or perivascular cells. Utilizing an established mouse model in which cre -dependent recombination constitutively-activates MAPK signaling within adult endothelium, we identify arteriole ECs as the driver of MAPK-mediated hematopoietic dysfunction. These results define complementary tamoxifen-inducible creER T2 -expressing mouse lines that label functionally-discrete and non-overlapping sinusoidal/transitional and arteriole EC populations in the adult BM, providing a robust toolset to investigate the differential contributions of vascular subtypes in maintaining hematopoietic homeostasis. Graphical Abstract

Restoration of herbivory on Caribbean coral reefs: are fishes, urchins, or crabs the solution? - Mark J. Butler; Alain Duran; Colette J. Feehan; Alastair R. Harborne; Alwin Hylkema; Joshua T. Patterson; William C. Sharp; Angelo Jason Spadaro; Tom Wijers; Stacey M. Williams (Frontiers in Marine Science, 2024)
That coral reefs are in decline worldwide, particularly in the Caribbean, will come as no surprise. This decades-long decline has reached a potential tipping point as the weight of the effects of climate change have come decidedly to bear on the planet’s most diverse marine ecosystem. Whether coral reefs can persist without restorative intervention is debatable, which has prompted a surge in coral reef restoration projects focusing primarily on the cultivation and transplantation of coral fragments onto degraded reefs. But that widespread approach does little to address the underlying causes of coral loss, one of which is the proliferation of macroalgae that are deleterious to corals. An emerging solution to this problem is the enhancement of herbivory on coral reefs through improved management of herbivores, artificial enhancement of herbivore settlement, or their mariculture and subsequent stocking. This review explores the nuances of the biology of well-studied Caribbean coral reef herbivores (fishes, sea urchins, and crabs) as it relates to their mariculture and investigates the promise of herbivore stocking onto coral reefs as a restoration strategy. Fish, urchin, and crab herbivores differ appreciably in life histories, which confers advantages and disadvantages with respect to their mariculture and effectiveness as grazers. Mariculture of herbivorous marine fish for reef restoration is essentially non-existent so the reestablishment of grazing fish abundance on coral reefs focuses primarily on their protection through fishery regulations, but only at a few locations in the Caribbean. Mariculture of herbivorous urchins and crabs for restoration purposes is in its infancy, but promising especially for crabs whose larval rearing is less difficult. Perhaps the biggest challenge for the mariculture of either taxon is “scaling-up” from research settings to large-scale mariculture needed for stocking. Numerous studies extol the benefits of functional redundancy and complementarity for coral reef ecosystem stability, but whether this principal applies to the restoration of grazing function is untested. We identify gaps in our knowledge of best practices for the restoration of grazing function on coral reefs and conclude with some practical guidance on the establishment of targets for macroalgal reduction, along with strategic advice on grazer stocking in a given reef habitat.

Air pollution and the sequelae of COVID-19 patients: A multistate analysis - Michael Jerrett; Claudia L. Nau; Deborah R. Young; Rebecca K. Butler; Christina M. Batteate; Ariadna Padilla; Sara Y. Tartof; Jason Su; Richard T. Burnett; Michael J. Kleeman (Environmental Research, 2023)

Animal population decline and recovery after severe fire: Relating ecological and life history traits with expert estimates of population impacts from the Australian 2019-20 megafires - Michelle Ensbey; Sarah Legge; Chris J. Jolly; Stephen T. Garnett; Rachael V. Gallagher; Mark Lintermans; Dale G. Nimmo; Libby Rumpff; Ben C. Scheele; Nick S. Whiterod; John C.Z. Woinarski; Shane T. Ahyong; et al. (Biological Conservation, 2023)

The conservation impacts of ecological disturbance: Time‐bound estimates of population loss and recovery for fauna affected by the 2019–2020 Australian megafires - Sarah Legge; Libby Rumpff; John C. Z. Woinarski; Nick S. Whiterod; Michelle Ward; Darren G. Southwell; Ben C. Scheele; Dale G. Nimmo; Mark Lintermans; Hayley M. Geyle; Stephen T. Garnett; Brittany Hayward‐Brown; et al. (Global Ecology and Biogeography, 2022)
Aim After environmental disasters, species with large population losses may need urgent protection to prevent extinction and support recovery. Following the 2019–2020 Australian megafires, we estimated population losses and recovery in fire‐affected fauna, to inform conservation status assessments and management. Location Temperate and subtropical Australia. Time period 2019–2030 and beyond. Major taxa Australian terrestrial and freshwater vertebrates; one invertebrate group. Methods From > 1,050 fire‐affected taxa, we selected 173 whose distributions substantially overlapped the fire extent. We estimated the proportion of each taxon’s distribution affected by fires, using fire severity and aquatic impact mapping, and new distribution mapping. Using expert elicitation informed by evidence of responses to previous wildfires, we estimated local population responses to fires of varying severity. We combined the spatial and elicitation data to estimate overall population loss and recovery trajectories, and thus indicate potential eligibility for listing as threatened, or uplisting, under Australian legislation. Results We estimate that the 2019–2020 Australian megafires caused, or contributed to, population declines that make 70–82 taxa eligible for listing as threatened; and another 21–27 taxa eligible for uplisting. If so‐listed, this represents a 22–26% increase in Australian statutory lists of threatened terrestrial and freshwater vertebrates and spiny crayfish, and uplisting for 8–10% of threatened taxa. Such changes would cause an abrupt worsening of underlying trajectories in vertebrates, as measured by Red List Indices. We predict that 54–88% of 173 assessed taxa will not recover to pre‐fire population size within 10 years/three generations. Main conclusions We suggest the 2019–2020 Australian megafires have worsened the conservation prospects for many species. Of the 91 taxa recommended for listing/uplisting consideration, 84 are now under formal review through national processes. Improving predictions about taxon vulnerability with empirical data on population responses, reducing the likelihood of future catastrophic events and mitigating their impacts on biodiversity, are critical.

Vascular Regulation of Hematopoietic Stem Cell Homeostasis, Regeneration, and Aging - Pradeep Ramalingam; Jason M. Butler; Michael G. Poulos (Current Stem Cell Reports, 2021)
Purpose of Review Hematopoietic stem cells (HSCs) sit at the top of the hierarchy that meets the daily burden of blood production. HSC maintenance relies on extrinsic cues from the bone marrow (BM) microenvironment to balance stem cell self-renewal and cell fate decisions. In this brief review, we will highlight the studies and model systems that define the centralized role of BM vascular endothelium in modulating HSC activity in health and stress. Recent Findings The BM microenvironment is composed of a diverse array of intimately associated vascular and perivascular cell types. Recent dynamic imaging studies, coupled with single-cell RNA sequencing (scRNA-seq) and functional readouts, have advanced our understanding of the HSC-supportive cell types and their cooperative mechanisms that govern stem cell fate during homeostasis, regeneration, and aging. These findings have established complex and discrete vascular microenvironments within the BM that express overlapping and unique paracrine signals that modulate HSC fate. Summary Understanding the spatial and reciprocal HSC-niche interactions and the molecular mechanisms that govern HSC activity in the BM vascular microenvironment will be integral in developing therapies aimed at ameliorating hematological disease and supporting healthy hematopoietic output.

Correlates of bird collisions with buildings across three North American countries - Jared A. Elmore; Stephen B. Hager; Bradley J. Cosentino; Timothy J. O'Connell; Corey S. Riding; Michelle L. Anderson; Marja H. Bakermans; Than J. Boves; David Brandes; Eric M. Butler; Michael W. Butler; Nicolette L. Cagle; et al. (Conservation Biology, 2021)
Collisions with buildings cause up to 1 billion bird fatalities annually in the United States and Canada. However, efforts to reduce collisions would benefit from studies conducted at large spatial scales across multiple study sites with standardized methods and consideration of species‐ and life‐history‐related variation and correlates of collisions. We addressed these research needs through coordinated collection of data on bird collisions with buildings at sites in the United States (35), Canada (3), and Mexico (2). We collected all carcasses and identified species. After removing records for unidentified carcasses, species lacking distribution‐wide population estimates, and species with distributions overlapping fewer than 10 sites, we retained 269 carcasses of 64 species for analysis. We estimated collision vulnerability for 40 bird species with ≥2 fatalities based on their North American population abundance, distribution overlap in study sites, and sampling effort. Of 10 species we identified as most vulnerable to collisions, some have been identified previously (e.g., Black‐throated Blue Warbler [ Setophaga caerulescens ]), whereas others emerged for the first time (e.g., White‐breasted Nuthatch [ Sitta carolinensis ]), possibly because we used a more standardized sampling approach than past studies. Building size and glass area were positively associated with number of collisions for 5 of 8 species with enough observations to analyze independently. Vegetation around buildings influenced collisions for only 1 of those 8 species (Swainson's Thrush [ Catharus ustulatus ]). Life history predicted collisions; numbers of collisions were greatest for migratory, insectivorous, and woodland‐inhabiting species. Our results provide new insight into the species most vulnerable to building collisions, making them potentially in greatest need of conservation attention to reduce collisions and into species‐ and life‐history‐related variation and correlates of building collisions, information that can help refine collision management.

The Instructive Role of the Bone Marrow Niche in Aging and Leukemia - Elisa Lazzari; Jason M. Butler (Current Stem Cell Reports, 2018)